No trade-offs in interspecific interference ability and predation susceptibility in newt larvae - Hloušková, Monika; Balogová, Monika; Kršáková, Veronika; Gvoždík, Lumír (Ecology and evolution, 2018)
Coexistence of species with similar requirements is allowed, among others, through trade-offs between competitive ability and other ecological traits. Although interspecific competition is based on two mechanisms, exploitation of resources and physical interference, trade-off studies largely consider only species' ability to exploit resources. Using a mesocosm experiment, we examined the trade-off between interference competition ability and susceptibility to predation in larvae of two newt species, Ichthyosaura alpestris and Lissotriton vulgaris. In the presence of heterospecifics, L. vulgaris larvae slowed somatic growth and developmental rates, and experienced a higher frequency of injuries than in conspecific environments which suggests asymmetrical interspecific interference. During short-term predation trials, L. vulgaris larvae suffered higher mortality than I. alpestris. Larvae of the smaller species, L. vulgaris, had both lower interference and antipredator performance than the larger I. alpestris, which suggests a lack of trade-off between interference competition ability and predator susceptibility. We conclude that interference competition may produce a positive rather than negative relationship with predation susceptibility, which may contribute to the elimination of subordinate species from common habitats.
Keywords: predator‐prey interaction; species coexistence; interspecific aggression; somatic growth; amphibians